Oral anticoagulants for coronary artery aneurysm: For few or for all?. Issue 5 (9th November 2021) - Gupta, Ankush; Seth, Ashok
Key Points: The management of coronary artery aneurysm (CAA) by medical treatment, percutaneous coronary intervention, or surgery remains arbitrary due to lack of large case series or trials. The "Coronary Artery Aneurysm Registry" represents the largest database and demonstrates decreased cardiac event rates with non‐significant increase in bleeding risk at intermediate term follow up by warfarin treatment. This strengthens the case for medical management of CAA and provides the basis for future follow‐up studies.